Pemanfaatan Metode Preference Selection Index Untuk Penilaian Dosen Terbaik Yang Diambil Dari Pengisian Kuesioner - Putri Aisyiyah Rakhma Devi (Universitas Budi Darma, 2023)
Muhammadiyah University conducts evaluations of the performance of the best lecturers using norms requiring students to fill out online surveys. But still using ordinary calculations and the occurrence of these calculations is not effective. Student assessment of lecturer teaching performance is the most frequent evaluation used in large learning to measure how well the course is being taught. The research phase begins with case identification, followed by data collection in the form of literature studies, surveys, and interviews. After data collection is complete, analysis is carried out using the PSI method to aid in calculations. Reports are then made according to the research results obtained. The criteria that were tried to evaluate the best Muhammadiyah University lecturers based on the assessment of the results of the questionnaire filled in by students were 4, namely Personality Competence, Pedagogic Competence, Professional Competence, and Social Competence. Based on the mechanism of the Preference Selection Index procedure to provide more efficient decisions, the implementation of this procedure is very simple and very easy to understand because each step helps in making decisions. The final result obtained from the PSI mechanism is 11.747.